CONDITION OF OPHTHALMOLOGIC APPEALABILITY BY PUPILS AND THEIR PARENTS CONCERNING MYOPIA - Lemberanskaya, A.Z. (World of Medicine and Biology, 2013)
Comprehensive ophthalmology and prospective survey show that a high prevalence of myopia among schoolchildren, its progressive nature of the flow is largely due to lower ophthalmologic appealability of parents. Timely diagnosis and corrective treatment of myopia stops the further deterioration of visual acuity, eliminates a discomfort condition among children.